2015
DOI: 10.1155/2015/627125
|View full text |Cite
|
Sign up to set email alerts
|

Gingiva Equivalents Secrete Negligible Amounts of Key Chemokines Involved in Langerhans Cell Migration Compared to Skin Equivalents

Abstract: Both oral mucosa and skin have the capacity to maintain immune homeostasis or regulate immune responses upon environmental assault. Whereas much is known about key innate immune events in skin, little is known about oral mucosa. Comparative studies are limited due to the scarce supply of oral mucosa for ex vivo studies. Therefore, we used organotypic tissue equivalents (reconstructed epithelium on fibroblast-populated collagen hydrogel) to study cross talk between cells. Oral mucosa and skin equivalents were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 43 publications
8
56
0
1
Order By: Relevance
“…This, together with the finding that anti-CXCL12 was unable to block migration, indicates that an as yet unknown chemokine / receptor pair is responsible for LC epithelium-to-LP migration in oral gingiva after allergen exposure. Indeed recently, we have shown that GE (without LC), topically exposed to an allergen or an irritant, secrete negligible amounts of key cytokines and chemokines (IL-18, CCL2, CCL20, CXCL12) involved in LC migration compared to skin, whereas the general inflammatory cytokine CXCL8 was secreted at similar levels by SE and GE (Kosten et al, 2015a). These results further support our current findings that the cytokines and chemokines triggering innate immunity and LC migration are very different in skin and gingiva.…”
Section: Lc Migration In Gingiva Is Cxcl12 Independentmentioning
confidence: 94%
See 2 more Smart Citations
“…This, together with the finding that anti-CXCL12 was unable to block migration, indicates that an as yet unknown chemokine / receptor pair is responsible for LC epithelium-to-LP migration in oral gingiva after allergen exposure. Indeed recently, we have shown that GE (without LC), topically exposed to an allergen or an irritant, secrete negligible amounts of key cytokines and chemokines (IL-18, CCL2, CCL20, CXCL12) involved in LC migration compared to skin, whereas the general inflammatory cytokine CXCL8 was secreted at similar levels by SE and GE (Kosten et al, 2015a). These results further support our current findings that the cytokines and chemokines triggering innate immunity and LC migration are very different in skin and gingiva.…”
Section: Lc Migration In Gingiva Is Cxcl12 Independentmentioning
confidence: 94%
“…Pro-inflammatory cytokines (e.g., TNFα, IL-α, IL-18) are rapidly released by epidermal cells and trigger the secretion of many chemokines from cells residing in the dermis, thus initiating the inflammatory response (Kosten et al, 2015a). One of these chemokines is CXCL12, which is secreted by dermal fibroblasts (Ouwehand et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both chemokines are lymphocyte chemo‐attractants (Morales et al, 1999) and CCL28 has high homology with CCL27 (Wang et al, 2000). Recently we have shown in another GS model (reconstructed epithelium on a fibroblast populated collagen hydrogel) that gingiva can indeed secrete CCL27 and that it is also inducible with tumour necrosis factor‐α, albeit to a much lower extent than in skin equivalents (Kosten, Buskermolen, Spiekstra, de Gruijl, & Gibbs, 2015). The reason why CCL28 was undetectable is currently unknown, but it is possible that it is directly internalized by other cells in the vicinity, such as fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings indicate that gingival LC in contrast migrate to the lamina propria in a CXCR4/CXCL12 independent fashion. In keeping with this, researchers found that CXCL12 was not secreted by gingival fibroblasts, not even after their activation [16], and that in gingival equivalents LC migrated to the lamina propria in a CXCL12 independent manner [34]. There are indications that LC in the oral mucosa may not even have to migrate to lymph nodes in order to direct a T cell immune response [35].…”
Section: Discussionmentioning
confidence: 99%